2013
DOI: 10.1007/978-1-4614-9135-4_8
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Control of Bioanalytical Methods

Abstract: The results of toxicokinetic, pharmacokinetic, and bioequivalence studies are used to make critical decisions regarding the safety and efficacy of anticancer drug substances. Therefore, measurement of anticancer drug concentrations in biological matrices is an important aspect in the development of these products. Such data are required by regulating agencies to support new drug applications as well as for line extensions and generic products of these drugs. It is therefore most essential to adequately charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…The interday precision was estimated from the analysis of the six standards on 5 separate days during the method validation. The intra-and interday precisions of sulindac sulfide were in the ranges of 2.9;10.6 and 6.3;9.0%, respectively, which was acceptable for all the quality control samples (Karnes et al, 1991).…”
Section: Methodsmentioning
confidence: 77%
“…The interday precision was estimated from the analysis of the six standards on 5 separate days during the method validation. The intra-and interday precisions of sulindac sulfide were in the ranges of 2.9;10.6 and 6.3;9.0%, respectively, which was acceptable for all the quality control samples (Karnes et al, 1991).…”
Section: Methodsmentioning
confidence: 77%
“…1). When accuracy and precision were separately evaluated as those could independently affect the concentration data (14), it was indicated that the larger analytical biases of the cross-validation samples analyzed at the receiving laboratories were caused by neither the analytical variation nor analytical biases in the bioanalytical methods used at the receiving laboratories with assuming that the analytical variation of a bioanalytical method could be estimated from the CV of the cross-validation samples (Figs. 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the precision of detection for both analytes was more than 85% and therefore within the interval set by the FDA concerning validation of bioanalytical methods. 29 Finally, the stability of stock solutions under storage conditions and the stability of extracted biological samples in the autosampler were tested and both (+)-and (−)-petromyroxol were stable for at least 1 month in the −20°C freezer and at least 48 hours in the 4°C autosampler (data not shown).…”
Section: Calibration and Methods Validationmentioning
confidence: 99%